Rapid Intra-operative Diagnosis of CNS Lymphoma on Squash & Imprint Smears – A Boon for the Surgeon: Case Report: CNS Lymphoma on crush & imprint smears - Sandhu, Azmat Kaur; Tyagi, Ruchita; Mittal, Amit; Selhi, Kanwarpal Singh; Kaur, Harpreet; Garg, Avantika; Kaushal, R K; Sood, Neena (Annals of Pathology and Laboratory Medicine, 2020)
Primary CNS Lymphoma [PCNL] accounts for 3% of all brain tumors. Diagnosing PCNL on squash and imprint cytology is a challenge for the pathologist but a boon for the operating surgeon as the knowledge of the nature of the lesion determines the nature of surgery. We report a case of 59 years old immunocompetent male who presented with right hemiparesis and headache. MRI Brain was suggestive of Left frontal Glioma. Intra-operatively, squash cytology and imprint smears of tissue from the lesion showed scattered lymphoid cells which also exhibited perivascular cuffing. Cytology was suggestive of lymphoma with differential of an inflammatory pathology. Histopathological examination and positivity for LCA, CD 20, Bcl 2 and Mum 1 on IHC confirmed the diagnosis of Diffuse Large B Cell Lymphoma-Brain. It is important to distinguish lymphoma from glioma or metastasis in CNS because of totally different lines of management. Knowledge of empirical diagnosis during surgery can guide the surgeon to ensure that adequate tissue is excised so that sample for immunophenotyping or further tests is available.